Law and Literature – a Meaningful Connection - Škop, Martin (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The connection between law and (imaginative) literature can still affect surprisingly. The theme of the present article is to summarize some of the basic features of the movement, which is called „Law and Literature” and to suggest some starting-points with which it is associated. These starting points include, for instance linguistic conception of law, narratology in law or the relations between law and culture. The article offers an overview of the classical approaches connecting law and literature and mentions the reasons for this connection: e.g. cultivation of law and lawyers, improvement of judicial decisions or improvement of legal interpretation. Some of the findings resulting from the joint of law and literature can be used in practice and goes beyond „mere” theory. The article is to be seen as an introduction to the movement of „Law and Literature”, presentation of ideas on which this movement is based and offering the possibility of its further development.